Using the particle swarm algorithm to build the master production scheduling for some products of Baghdad company of soft drinks - Hamza, Teba S.; Said, Asfad M.; Mohammed, Nashaat J. (AIP conference proceedings, 2024)
The master production scheduling (MPS) is the attachment between planning and manufacturing, being applied as the ground for defining the capacity and resources wanted to obtain production plans. Here we used the particle swarm optimization algorithm (PSO) to get MPS for two products of Baghdad company of soft drinks. a python code is used in calculation aspects. The results obtained using the particle swarm optimization algorithms were compared with the results obtained according to the mechanisms of the Baghdad Company for soft drinks. The results showed a clear superiority in favour of the particle algorithm.